PENGARUH KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Study Kasus Pada Wajib Pajak Orang Pribadi Pada KPP Probolinggo) - Ayu Fitri Anggraini; Afifudin Afifudin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
Indonesia is a country that has a very dense population. The Republic of Indonesia implements national development in all fields carried out in a comprehensive and sustainable program for the achievement of the national development goals, namely creating a just and prosperous society. The implementation of this national development requires a very large amount of investment both from within and outside the country. These funds are obtained by the government both from within and outside the country.Taxes are an important aspect in the development process of a country, especially in Indonesia, so development aims to realize and improve the welfare of a nation, in this case the role of taxes as a source of financing in the development of a country.Based on the statement of the Director General of Taxes, Robert Pakpahan, state revenue from PPN and PPnBM until September 2018 grew to 64.88% or Rp. 351 trillion. The Ministry of Finance itself has noted that, until the end of November 2018, the realization of state revenues from taxes reached 79.82% of the 2018 State Budget target or amounting to Rp1,136.66 trillion. This figure allegedly grew by 15.35% from tax revenue in the same period in the previous year. Tax revenue is one of the state revenues that provides the largest contribution to financing expenditures and state development as owed in the State Budget (APBN). Realizing how big the role of taxes is, the government, in this case the Directorate General of Taxes under the auspices of the Ministry of Finance, continues to make various strategic and effective efforts to maximize tax revenue (Ariesta, 2017). Keywords: awareness of taxpayers and tax sanctions against personal taxpayer compliance